2004
DOI: 10.1515/jpem.2004.17.4.601
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Deficiency in Patients with Sickle Cell Disease and Growth Failure

Abstract: GH deficiency may be associated with growth failure in some patients with SCD. These patients may benefit from treatment with GH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 7 publications
0
25
0
1
Order By: Relevance
“…[26][27][28][29][30][31] Growth hormone deficiency may account for a small percentage of children with SCD who have severe growth delay. 32 Hemolysis, chronic anemia, and a high metabolic rate appear to be the most significant adverse factors for growth in SCD. Resting energy expenditure was increased in several studies of children with SCD and is probably related to anemia, chronic inflammation, high cardiac output, and high protein turnover.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29][30][31] Growth hormone deficiency may account for a small percentage of children with SCD who have severe growth delay. 32 Hemolysis, chronic anemia, and a high metabolic rate appear to be the most significant adverse factors for growth in SCD. Resting energy expenditure was increased in several studies of children with SCD and is probably related to anemia, chronic inflammation, high cardiac output, and high protein turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in gonadotropin secretion patterns (elevated luteinizing hormone and depressed follicle-stimulating hormone in early puberty) in boys and girls with SCD (19) and poor testosterone response to gonadotrophin-releasing hormone in some boys (20) suggest impairments in the regulatory feedback mechanisms of the hypothalamic-pituitary-gonadal axis leading to sexual maturity. Growth hormone abnormalities have also been reported (21)(22)(23).…”
Section: Growth Failure In Sickle Cell Diseasementioning
confidence: 93%
“…An international inquiry showed that these tests were recommended in most countries with guidelines for diagnostic work up [36]. The available literature shows that there is a strong relationship between thalassemia, sickle cell disease and growth retardation [127][128][129][130]. Likewise, Stephensen et al showed evidence of the association between infectious diseases and linear growth [131].…”
Section: The Diagnostic Processmentioning
confidence: 99%